Respon Pertumbuhan Tanaman Anggrek Bulan (Phalaenopsis amabilis) Terhadap Perlakuan Media Tanam dan POC Kulit Bawang Merah (Allium cepa) - Firdaus El Salama, Shaila; Ngadiani; Andriani, Vivin (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2024)
Moon orchid (Phalaenopsis amabilis) is one of the most fascinating orchid genus. The variety of colors, shapes and textures, as well as the aroma make moon orchids one of the most beautiful flowers. Ferns contain elements of Nitrogen (N), Carbon (C), Hydrogen (H), and silica. Coconut shells contain carbohydrates (K), phosphorus (P), sodium (Na) and magnesium (Mn). Shallots (Allium cepa) contain the elements Potassium (K), Calcium (Ca), Nitrogen (N), Phosphorus (P), Iron (Fe), Manganese (Mg), Magnesium (Mn), and Zinc (Zn). Meanwhile, non-nutritive chemical compounds include auxin and gibberellin hormones. This study used the complete randomized design (CRD) method, which consisted of 18 treatments and 3 replications. The growth parameters observed were number of leaves, leaf area, root length, plant weight, and survival rate. Based on the results of this study, it is concluded that the provision of planting media and shallot skin POC treatment affects the growth of moon orchids. The results of Duncan's test showed the M3P4 treatment combination (chopped fern + coconut shell) and shallot skin POC (30%) produced the best growth in the parameter of root length of 5.16 cm and plant weight of 2.82 grams. However, it has no effect on the number of leaves and leaf area. Keywords: Moon orchid; Growing media; POC; Chopped fern, coconut shell; Shallot skins.